PENGARUH KOMPETENSI, DISIPLIN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA DAERAH PROVINSI SULAWESI TENGAH - Daly, Hamlan (Katalogis, 2015)
This research aims to: (1) provide description of competency, dicipline, compensation personnel performance at regional office of women empowerment and family planning, Central Sulawesi Province; (2) know and analyze simultaneous effect of competency, dicipline, compensation on personnel performance at regional office of womenÂ empowermentÂ and family planning, Central Sulawesi Province; (3) know and analyze the effect of competency on personnel performanceÂ at regional office of women empowerment and family planning, Central Sulawesi Province; (4) know and analyze the effect of dicipline on personnel performance at regional office of women empowerment and family planning, Central Sulawesi Province; (5) know and analyze the effect of compensation on personnel performance at regional office of women empowerment and family planning, Central Sulawesi Province. This research involves 55 personnel that have been determined using census method. The results of multiple linear regression show that competency, dicipline, compensation simultaneously and partially perform positive and significant effects on personnel performance at regional office of women empowerment and family planning, Central Sulawesi Province.